2013
DOI: 10.1007/s00221-013-3467-7
|View full text |Cite
|
Sign up to set email alerts
|

Grasping in wonderland: altering the visual size of the body recalibrates the body schema

Abstract: Can viewing our own body modified in size reshape the bodily representation employed for interacting with the environment? This question was addressed here by exposing participants to either an enlarged, a shrunken, or an unmodified view of their own hand in a reach-to-grasp task toward a target of fixed dimensions. When presented with a visually larger hand, participants modified the kinematics of their grasping movement by reducing maximum grip aperture. This adjustment was carried over even when the hand wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 36 publications
2
22
0
Order By: Relevance
“…Thus, recalibration of the representation of the hand was not a necessary requirement when judging the location of the hand (i.e. proprioceptive drift) (Bernardi et al 2013; de Vignemont 2011; Linkenauger et al 2013). …”
Section: Discussionmentioning
confidence: 99%
“…Thus, recalibration of the representation of the hand was not a necessary requirement when judging the location of the hand (i.e. proprioceptive drift) (Bernardi et al 2013; de Vignemont 2011; Linkenauger et al 2013). …”
Section: Discussionmentioning
confidence: 99%
“…Performance gains increased with the size of the virtual hands but only in the context of visual feedback, when the subjects actively controlled the virtual hand and not in the context of visual input (as in training by observation). Previous studies in motor control showed that participants changed their hand kinematics following changes in hand-size visual feedback [26, 27]. To the best of our knowledge, the current study is the first to demonstrate that rescaling the visual feedback during training can boost the motor performance in humans.…”
Section: Discussionmentioning
confidence: 49%
“…The size of visual feedback from the body has been previously examined in various domains including pain perception [17, 18, 20], tactile discrimination [13], sense of embodiment [14, 15], and reaching/grasping tasks [26, 31] but not with respect to short term motor skill learning. Here we used VR devices to manipulate the size of virtual hands controlled by the subject, embedded in the real environment as captured by a camera.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Visual information on the size of the body is accessed by the body schema and is prioritized over proprioceptive inputs for motor control [13]. Articular proprioception, defined as a specialized sensory function that includes the sensation of movement and joint position, must integrate with visual afferents for correct static and dynamic joint activity [14, 15].…”
Section: Introductionmentioning
confidence: 99%